2013
DOI: 10.4236/jct.2013.46a2003
|View full text |Cite
|
Sign up to set email alerts
|

Assessing Colorectal Cancer Screening Behaviors and Knowledge among At-Risk Hispanics in Southern New Mexico

Abstract: Purpose Colorectal cancer (CRC) mortality rates in New Mexico (NM) continue to be higher than national rates. Hispanic CRC mortality rates in NM surpass those of overall Hispanics in the US. This study was designed to characterize and understand factors contributing to low CRC screening rates in this border region. Methods A CRC Knowledge Assessment Survey (KAS) was administered in either English or Spanish to 247 individuals attending community events throughout southern NM. A subset of these individuals co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
14
1
2

Year Published

2016
2016
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 25 publications
(19 citation statements)
references
References 27 publications
2
14
1
2
Order By: Relevance
“…More worrisome is the fact that statistics continue to show increasing trends in both incidence and mortality rates as well as low adherence to CRC screening rates, despite the existence of guidelines and methods that would increase detection at earlier, more treatable stages. Lack of knowledge has been associated and described as a significant barrier for CRC screening [14-16]. The present study evaluated CRC knowledge among a group of Puerto Rican Hispanic adults, and found a high proportion of adults with inadequate CRC knowledge.…”
Section: Discussionmentioning
confidence: 79%
See 2 more Smart Citations
“…More worrisome is the fact that statistics continue to show increasing trends in both incidence and mortality rates as well as low adherence to CRC screening rates, despite the existence of guidelines and methods that would increase detection at earlier, more treatable stages. Lack of knowledge has been associated and described as a significant barrier for CRC screening [14-16]. The present study evaluated CRC knowledge among a group of Puerto Rican Hispanic adults, and found a high proportion of adults with inadequate CRC knowledge.…”
Section: Discussionmentioning
confidence: 79%
“…It has been previously reported that knowledge and awareness of CRC in the general population is low [11-13], which is a significant barrier for CRC screening compliance especially among Hispanics [14-16]. Limited health literacy has been associated with less knowledge about CRC and CRC screening [17].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Thus, it is also of great importance to evaluate the risk factors for which measures must be taken, like smoking, alcohol use, obesity, low-level physical activity, nutritional habits, and genetic factors [8].…”
Section: Introductionmentioning
confidence: 99%
“…The finding in the southeast parts of New Mexico was consistent with previous studies. [25–27] These studies found that low CRC screening rate in New Mexico may be associated with transformative and/or stigmatizing embarrassment, fear of pain and discomfort, low CRC knowledge, insufficient patient–physician discussion, and lack of health insurance. At the US national level, the lack of health insurance, area-level poverty rate, and out-of-pocket expenditures were reported as significant predictors of low screening rate for CRC screenings.…”
Section: Discussionmentioning
confidence: 99%